Evaluations of Accounting Journal and Department Quality. - Weber, Richard P.; Stevenson, W. C. (The Accounting Review, 1981)
Abstract ABSTRACT: Over the past few years, several articles appearing in The Accounting Review have dealt with ranking journals based on "perceived quality" and accounting departments based on publications in "leading" journals. This paper identifies some questionable assumptions underlying earlier studies and provides journal quality evaluations which may be used in discriminating among accounting departments.